Postanoxia-Induced Chorea Treated with Intravenous Fentanyl - Ashley Audi; Brittany Cunningham; Christopher Newey (Case Reports in Neurological Medicine)
The case presented is that of a young male with postanoxic brain injury secondary to cocaine overdose who began to exhibit choreiform movements of the left upper extremity. Traditional treatment options for chorea were unsuccessful, leading to the administration of fentanyl, which rapidly resolved the patient’s choreiform movements. There is a limited research involving the treatment of chorea in anoxic brain injury as well as fentanyl’s role in the movement pathway. We hypothesize that chorea can be caused or exacerbated by opioid withdrawal in a patient with chronic opioid use through modulation of dopamine transmission.